Rapid Inoculation Technique and Biological Control of Leaf Spot Disease in Oil Palm - Delia Agustina; Cahya Prihatna; Antonius Suwanto (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2019)
Oil palm (Elaeis guineensis) is one of the most efficient oil-producing crops in the world. However, fungal diseases such as basal stem rot (BSR) caused by Ganoderma sp. causes significant loss to the yield of adult palms. Apart from BSR, leaf spot disease caused by Curvularia sp. also causes significant loss during nursery stages. In this study, Curvularia sp. was isolated from a diseased palm seedling and a rapid and reproducible artificial inoculation method was developed. The technique has bioassay to determine the level of success of the control of leaf spot disease in a glasshouse setting. A natural, organic cyclic peptide fungicide and living cells of a bacterial strain Paraburkholderia sp. CP01 were tested for their efficacy to control leaf spot in oil palm seedlings. The severity of leaf spot disease in oil palm seedlings treated by organic cyclic peptide fungicide and CP01 was significantly lower than untreated control, indicating potential biological control agents. The results presented here provide technical reference and novel approach to controlling leaf spot disease of oil palm.